2002
DOI: 10.1002/app.11452
|View full text |Cite
|
Sign up to set email alerts
|

Rice husk ash filled natural rubber. I. Overall rate constant determination for the vulcanization process from rheometric data

Abstract: Black rice husk ash (BRHA) and white rice husk ash (WRHA) were incorporated into natural rubber (NR) using a laboratory-size two-roll mill. A conventional vulcanization system (CV) was chosen and cure studies were carried out on a TI-100 Curometer. The torque curves were obtained at 150, 160, 170, and 180°C. The overall rate and the apparent activation energy for the vulcanization process were calculated for each compound assuming that vulcanization follows first-order kinetics. For comparison purposes, two co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
17
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 61 publications
7
17
0
1
Order By: Relevance
“…These metal oxides are aluminum oxide (Al 2 O 3 ), ferrum oxide (Fe 2 O 3 ), rubidium oxide (Rb 2 O), and so forth. The presence of these metal oxides might enhance the curing rate of vulcanizates of rubber 13. Table III shows the chemical composition of palm ash according to a Rigaku RIX 3000 X‐ray fluorescence spectrometer.…”
Section: Resultsmentioning
confidence: 99%
“…These metal oxides are aluminum oxide (Al 2 O 3 ), ferrum oxide (Fe 2 O 3 ), rubidium oxide (Rb 2 O), and so forth. The presence of these metal oxides might enhance the curing rate of vulcanizates of rubber 13. Table III shows the chemical composition of palm ash according to a Rigaku RIX 3000 X‐ray fluorescence spectrometer.…”
Section: Resultsmentioning
confidence: 99%
“…Reinforcement with fillers from renewable resources into polymeric materials has become a major interest in recent years. According to reports, lots of fillers have been used to take the place of the commonly used carbon black; these include silicates, montmorillonite, and reinforcing fillers from renewable resources such as rice husks, starch, chitosan, oil palms, chitin, and cuttlebones …”
Section: Introductionmentioning
confidence: 99%
“…In other work, Costa et al [82] evaluated the vulcanization process of NR filled with BRHA (75 wt.% SiO2, 21 wt.% LOI, 17 m 2 /g) and WRHA (97 wt.% SiO2, 0.2 wt.% LOI, 109 m 2 /g). They reported that the vulcanization process was accelerated in the presence of WRHA, whereas the BRHA filler did not present a significant effect.…”
Section: Rha /Elastomers Compositesmentioning
confidence: 99%
“…This fact was attributed to differences in filler properties, such as surface area, surface activity, pH, particle size, moisture content, and metal content. Furthermore, the ZnO added to the composites may led to accelerate the vulcanization process [81], [82].…”
Section: Rha /Elastomers Compositesmentioning
confidence: 99%